Comparison of Effects of Inhaled Salbutamol with Placebo in Management of Transient Tachypnea of Newborn - Khaista Rehman; Fahim Ahmed Subhani; Sajid Ali Shah; Bilal Ahmed; Ammara Ayub; Saba Afzal Sheikh (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the outcome of inhaled Salbutamol (Albuterol) with normal saline (Placebo) in terms of mean duration of oxygen therapy and mean hospital stay in newborns with transient tachypnea of the newborn.